Aprendizagens nas brincadeiras de crianças de 2 anos na educação infantil: análise dos processos de desenvolvimento cultural - Silva, Eliane Nicolau da (2015)
The importance of research about cultural development of children in kindergarden is configured understand deeply and scientifically how children are appropriating knowledge through social relations. We focus on the cultural development of two years old children, by way of plays, that in the theoretical framework adopted, the Historical and Cultural Theory, this activity is driving psychic development in this age group. Therefore, the research question that guided this study was: what show us the play of children about their cultural development? From this, we delineated these following objectives: to identify and analyze the appropriation process of social relations of two years old children, which compose the cultural infant development, through the analysis of their play; to discuss these processes of cultural, development in relation to children s learning of this age. This research is qualitative in nature and effected in a unit of Early Childhood Education located in an upcountry city on the State of São Paulo. The main tool of data collected was the video recording and, to complement this technique, some recordings were make every day. We realized the analysis using the microgenetic approach Vigotsky. The results show that children reveal important information about their development while play and this this knowledge appropriation begin very early. The conclusions of this research contribute to the educational area as a source of theoretical and practical knowledge.